1993
DOI: 10.1002/ajmg.1320470232
|View full text |Cite
|
Sign up to set email alerts
|

Two siblings with midline field defects and Hirschsprung disease: Variable expression of Toriello‐Carey or new syndrome?

Abstract: We describe 2 sibs with multiple congenital anomalies. The main manifestations include hypoplasia of the corpus callosum and/or cerebellar hypoplasia, Robin sequence, pharyngeal and laryngeal hypoplasia, abnormal ears, excessive neck skin, cardiac defect, and Hirschsprung disease. The presence in 2 sibs born to healthy, consanguineous parents suggests autosomal recessive inheritance. These anomalies must have arisen during blastogenesis; the syndrome resembles most the condition described in 1988 by Toriello a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 4 publications
4
21
0
Order By: Relevance
“…Positional anomalies of the foot and hypermobility of the joints observed in our siblings were also occasionally recorded [Jespers et al, 1993;Chinen et al, 1999;Ohta et al, 1999;Aftimos and McGaughran, 2001]. Brachydactyly is common in Toriello-Carey syndrome, but short upper limbs and synostosis of the metacarpal bones are previously unreported findings.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Positional anomalies of the foot and hypermobility of the joints observed in our siblings were also occasionally recorded [Jespers et al, 1993;Chinen et al, 1999;Ohta et al, 1999;Aftimos and McGaughran, 2001]. Brachydactyly is common in Toriello-Carey syndrome, but short upper limbs and synostosis of the metacarpal bones are previously unreported findings.…”
Section: Discussionmentioning
confidence: 59%
“…So far 16 cases have been reported [Lacombe et al, 1992;Camera et al, 1993;Jespers et al, 1993;Czarnecki et al, 1996;Till et al, 1997;Chinen et al, 1999;Ohta et al, 1999;Aftimos and McGaughran, 2001;Wegner and Hersh, 2001]. Czarnecki et al [1996] indicated an unbalanced sex ratio and proposed an Xlinked or sex-influenced mode of inheritance.…”
Section: Introductionmentioning
confidence: 95%
“…Three of those children were sibs; the fourth was an isolated case. Since that time, 16 additional patients have been published [Lacombe et al, 1992;Camera et al, 1993;Jespers et al, 1993;Czarnecki et al, 1996;Till et al, 1997;Chinen et al, 1999;Ohta et al, 1999;Aftimos and McGaughran, 2001;Wegner and Hersh, 2001;Paladini et al, 2002;Barisic et al, 2003]. We have also had the opportunity to review over 40 unpublished patients, although we believed that some of these individuals did not have Toriello-Carey syndrome.…”
Section: Introductionmentioning
confidence: 88%
“…Distal limb abnormalities are largely represented by polydactyly and limb hypoplasia but may also be associated with congenital deafness [68] or cardiac anomalies [69,70]. Polydactyly has been described as part of a syndrome of heart defects, laryngeal anomalies and HSCR [70,71] and other autosomal recessive syndromes in siblings [68]. HSCR has been associated with Werner mesomelic dysplasia [72], short stature [73] and the BRESHEK syndrome [74].…”
Section: Intestinal Atresiamentioning
confidence: 99%